The Geoboard Teaching Aid on Similarity and Symmetry Topics for Elementary School Students - Abdussakir Abdussakir; Ainur Firmansyah; Dewi Rosikhoh; Nur Laili Achadiyah (Edumatika : Jurnal Riset Pendidikan Matematika, 2022)
Learning media in the form of teaching aids was necessary for learning in elementary schools caused students in this grade were in the concrete operational stage. This study aimed to determine the feasibility, attractiveness, and effectiveness of the Geoboard teaching aid on similarity and symmetry topics for fifth-grade of elementary school students. The development of the Geoboard teaching aid in this study used the Borg and Gall model. Subjects of feasibility consisted of three experts and one practitioner, attractiveness subjects consisted of 6 students, and effectiveness subjects consisted of fifth-grade students in one public elementary school in Mojokerto, East Java. The results showed that the feasibility of the Geoboard teaching aid on similarity and symmetry topics obtained a percentage score of 91% on the material aspect, 96% on the media design aspect, 90% on the mathematics learning aspect, and 90% on the practical aspect. The percentage of the attractiveness test score reached 99.03%. The data analysis results by independent sample t-test showed that the Geoboard teaching aid significantly improved student learning outcomes. Overall, it could conclude that the Geoboard teaching aid on similarity and symmetry topics was feasible, attractive, and effective for fifth-grade students.